PEMBERDAYAAN MASYARAKAT MELALUI PEMBANGUNAN PARIWISATA UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA KARANGSARI - Maida, Serepina Tiur; Sarwoko, Tri Adi; Muratin, Muratin; Sudibyo, Sudibyo; Ginting, JP (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
The construction and development of Karang Sari Village to become a tourist village is very important. Seeing that so far this potential has not been exploited and organized and it is hoped that it will be able to improve the economic and welfare of the community. Karang Sari Village has a stretch of beach of approximately 17 km, from Muara Cimari beach to Cicalengka beach. Karang Sari Village has a stretch of beach of approximately 17 km, from Muara Cimari beach to Cicalengka beach. Indonesian tourism development uses the concept of cultural tourism formulated in Tourism Law Number 09 of 1990. The problem is that villages are still in the underdeveloped category, low levels of community welfare and low levels of facilities and infrastructure as well as knowledge in managing village potential. The aim is to increase the quality and quantity of tourism destinations to create a tourism industry that is able to drive the local and national economy, develop tourism institutions and tourism governance that are able to synergize tourism destination development, tourism marketing and the tourism industry in a professional, effective and efficient manner. Using the perspective of communication science theory from Professor John Marston (in Nova, 2009:32) regarding planning strategies, namely RACE (Reasearch, Action, Controling, Evaluation). Community service activities are analyzed using SWOT analysis (Strength, Weakness, Opportunity, Threat). In conclusion, building tourism potential in underdeveloped villages must review all aspects. Looking at the potential of natural resources and human resources, but looking at the geographical conditions and geopolitical conditions in the Karangsari Village area. Suggestions, Village Head and Karangsari Village Apparatus, persuasive efforts for people who still do not understand and take a counter stance towards the idea of building a tourist village